Місце центрального банку в системі органів державної влади - Устименко, Г. В. (My University, 2011)
З оглядово-узагальнюючого боку розглянуто місце центрального банку в системі органів державної влади, його взаємодія з органами державної влади. Аналізуються функції та статус Національного банку, обґрунтовуються положення Конституційних норм щодо центрального банку держави. From a generalizing perspective, the place of the central bank in the system of state authorities and its interaction with state authorities are considered. The functions and status of the National Bank are analyzed, and the provisions of the Constitutional norms regarding the state's central bank are substantiated.
Keywords: центральний банк; central bank; державна влада; state power